Pengaruh Penyaluran Kredit Terhadap Laba Bersih Pada PT. Bank Danamon Tbk - Akal, Andi Tenri Uleng; Nur, Sri Wahyuni (Universitas Patria Artha, 2022)
This study aims to determine the effect of lending on net income at PT Bank Danamon Tbk listed on the Indonesia Stock Exchange. This type of research is classified as quantitative research, while the source of data in this study is secondary data in the form of the company's annual financial statements of PT Bank Danamon Tbk for the period 2017-2021. The analytical method used in this research is simple linear regression, correlation coefficient, determination test, t test. The results showed that the distribution of credit at PT Bank Danamon Tbk had no effect on net income. The correlation coefficient is 0.535, which means that the relationship is moderate, the determination test is 28.6% and the remaining 71.4% is influenced by other factors. The significance value is 0.3530.05.